Microbiomes of Healthy and Bleached Corals During a 2016 Thermal Bleaching Event in the Andaman Sea of Thailand - Chavanich, Suchana; Kusdianto, Heru; Kullapanich, Chitrasak; Jandang, Suppakarn; Wongsawaeng, Doonyapong; Ouazzani, Jamal; Viyakarn, Voranop; Somboonna, Naraporn (Frontiers in Marine Science, 2022)
As seawater temperature rises, repeated thermal bleaching events have negatively affected the reefs of the Andaman Sea for over decades. Studies on the coral associated microbial diversity of prokaryotes and microbial eukaryotes (microbiome) in healthy and bleached corals are important to better understand the coral holobionts involved augmented resistance to stresses; and this information remains limited in the Andaman Sea of Thailand. The present study thereby described the microbiomes of healthy (unbleached) and bleached colonies of four prevalent corals Acropora humilis, Platygyra sp., Pocillopora damicornis and Porites lutea, along the surrounding seawater and sediments, that were collected during a 2016 thermal bleaching event, using 16S and 18S rRNA genes next generation sequencing (NGS). Both prokaryotic and eukaryotic microbes showed isolated community profiles among sample types (corals, sediment and seawater) (ANOSIM: P = 0.038 for prokryotes, P < 0.001 for microbial eukaryotes), and among coral genera (ANOSIM: P < 0.001 for prokryotes and microbial eukaryotes). In bleached state corals, we found the differences in microbial compositions from the healthy state corals. Prevalent differences shared among bleached coral genera (shared in at least three coral genera) included a loss of reported coral-beneficial microbes, such as Pseudomonadales, Alteromonadales and Symbiodinium; meanwhile increase of putative coral-pathogenic Malassesia and Aspergillus. This difference could affect carbon and nitrogen availability for coral growth, reflective of healthy or bleached state. Our findings in part supported previously microbial dysbiosis knowledge of thermal bleaching coral microbiomes around South East Asia marine geography.